Holder Norsk politiutdanning mål (slik politiet selv vurderer den)? - Geir Aas; Gunnar Thomassen; Annette Sund (Nordisk Tidsskrift for Kriminalvidenskab)
Abstract The Norwegian Police University College is required to regularly evaluate and ensure the quality of the education in order to maintain its accreditation as an institution of higher education. A central aspect of this quality control is to make sure that the education is relevant for the field of practice and the policing profession. The Police University College has therefore on three occasions since 2006 sent out a survey to police officers three years after graduation and asked them to evaluate the relevance of the education in general, and more specifically to evaluate their own qualifications in different areas of competence. A similar questionnaire was sent to the supervisors of the post-graduates to get a broader comparative perspective.